Determination of Properties of Cadmium, Cobalt, Manganese and Copper Complexes with 1-(6-Bromo-2-Benzothiazolylazo)- 2-Naphthol. - GAO, HONG-WEN; HONG, CHANG-LIANG; SHI, SHU-REN (Asian Journal of Chemistry, 2010)
The updated determination method of properties of several metal complexes was reported recently. The reactions were studied between four metals: Cd(II), Co(II), Mn(II) and Cu(II) and 1-(6-bromo-2- ,benzothiazolylazo)-2-naphthol (BBTAN) at pH II. The β-correction method was used instead of the ordinary spectroatphotometry, because of the influence on each other of free ligand and its complex. The composition ratios, the stepwise real molar absorptivity (ε) and stepwise or cumulative stability constant. (K) of M-BBTAN (M = Cd, Co, Mn or Cu) complexes were all worked out. The recommended method was more acceptable in principle and simpler in operation than the classical method.